Diagnosis of thalassemia using fluorescence spectroscopy, auto-analyzer, and hemoglobin electrophoresis - A prospective study - Sandhanasamy Devanesan; Fatma AlQahtani; Mohamad S. AlSalhi; Karuppaiah Jeyaprakash; Vadivel Masilamani (Elsevier, 2019)
Background: Hemoglobinopathies (HgP) are prevalent in certain regions of the world. The World Health Organization estimated that 5% of the world's population is a carrier of the potentially pathological hemoglobin (Hb) gene. Methods: This study aimed to compare the performance of fluorescence spectroscopy, a simple and inexpensive method, with that of conventional techniques for diagnosing thalassemia. The red blood cell (RBC) counts and levels of Hb, HbA, HbA2, and HbS were estimated via conventional methods of complete blood count and Hb electrophoresis to diagnose thalassemia. Results: The RBCs and Hb, particularly the average values of HbA and HbA2, were lower in patients with thalassemia than in the normal controls. These hematologic parameters were also analyzed via fluorescence spectroscopybased on fluorescent biomolecules including tyrosine (275 nm), tryptophan (290 nm), nicotinamide adenine dinucleotide (NADH) (370 nm), flavin adenine dinucleotide (FAD) (450 nm), and porphyrin (585-635 nm). In thalassemia patients, all these parameters were above the normal range, primarily due to abnormal depression of NADH and elevation of FAD. Conclusion: Thalassemia canbe diagnosed via a fluorescent spectral method with an accuracy of 85% for blinded groups. This method may be useful for screening patients and reducing the cost of diagnosis in many rural countries. Keywords: Thalassemia, Spectral methods, Fluorescent biomolecules, Conventional methods